AN INVESTIGATION OF OXIDES OF NITROGEN IN METROPOLITAN TEHRAN - M.Ghiassedin; K.Imandel; A.Vakhideh (Tehran University of Medical Sciences, 1978)
Planning of air pollution control programs need knowledge of pollutants emitting sources; the Department of Environmental Health, School of Public Health, Tehran University, performed an air monitoring program for a period of six months in 1976-77. A daily sampling was done from 8 a.m. to 8 p.m., at ten different stations in metropolitan Tehran. Saltzman's sampling and analysis procedures were employed in this investigation. Here are the main results drawn from this conduction. Monthly trend of Nox concentration shows a decrease from September through February. The highest concentration of Nitrogen Oxides was observed at Railway Station Square that was about 2.2 times more than the University. The Nox concentration ranged between 0.17 to 0.62 ppm at Rail-Station Square (maximum) and 0.04 to 0.21 ppm at University (minimum). The hourly fluctuation shows two peaks of maximum concentration.